A new species and a new record of Phanoperla (Plecoptera: Perlidae) from Yunnan, China - Zeng, Liang-Liang; Huo, Qing-Bo; Du, Yu-Zhou (Zootaxa, 2025)
Phanoperla menglunensis sp. nov. (Plecoptera: Perlidae) is described from Yunnan Province, China. Additionally, we present the first Chinese record of P. uchidai Sivec & Stark, 2010, previously known only from Thailand and Laos. An updated description of P. uchidai is also provided, supplemented with diagnostic imagery for clarity.